Rational mate choice decisions vary with female age and multidimensional male signals in swordtails. (25th June 2018) - Reding, Luke; Cummings, Molly E.
Abstract: Biologists have long been interested in intransitive preferences: circular preferences in which options cannot be ranked and no single option dominates, similar to a game of rock‐paper‐scissors. Intransitive preferences violate rational decision‐making, an assumption made by models of evolution by mate choice. Despite its potential importance in the study of sexual selection, few studies have tested for intransitive preferences. Even fewer have asked whether females differ in whether they choose mates transitively or intransitively and what factors might predict (in)transitive choice. Though intransitive choice is thought to be more common as options become more complex, this prediction is untested in animals. To fill this gap, we tested whether female Xiphophorus nigrensis swordtails can rank digitally animated males differing in size, courtship intensity, or both size and courtship intensity, and whether female responses were predicted by a female's age. Females choosing among males that varied only in size showed higher than expected levels of intransitivity, whereas females choosing among males that varied in their courtship or both properties did not. Older females were more likely to be irrational than younger females when evaluating male size, suggesting that experience modifies transitive decision‐making processes. These results show that mate choice irrationality may vary by a female's experience and the signal characteristics during decision‐making.